Fermentation of Banana Stems and Indigofera sp. Using MA-11 with Different Durations on Physical Quality - Taufik Ferdiansyah; Ludfia Windyasmara (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The high cost of ruminant feed and fluctuating forage availability have encouraged the use of local waste, such as banana stems, combined with Indigofera sp. through fermentation with the probiotic MA-11 to improve the feed's pHysical quality and pH. This study aimed to determine the effect of fermentation time (0, 3, 6, 9, and 12 days) on the texture, aroma, color, and pH of the mixture to determine the optimal time for use as an alternative feed based on agricultural waste. The study used a completely randomized design with five treatments and four replications, conducted over 12 days in the Microbiology Laboratory of the Faculty of Agriculture, Veteran Bangun Nusantara University, Sukoharjo. Testing involved panelist assessments for pHysical quality and periodic pH measurements. The results showed a highly significant effect of fermentation time on all parameters, with a 9-day treatment producing a soft texture, fresh sour aroma, yellowish-brown color, and an optimal low pH. A 9-day fermentation with MA-11 yields high-quality feed from local waste.